Protective role of quercetin against lead-induced inflammatory response in rat kidney through the ROS-mediated MAPKs and NF-κB pathway - Liu, Chan-Min; Sun, Yun-Zhi; Sun, Jian-Mei; Ma, Jie-Qiong; Cheng, Chao (Biochimica et biophysica acta, 2012)
Lead (Pb) exposure is considered as a risk factor for the development of renal dysfunction. The flavonoid quercetin (QE) in diets exerts the nephroprotective effects. This study investigated the effects of quercetin on renal oxidative stress and inflammation in rats exposed to Pb. Wistar rats were divided into normal, lead exposure groups, lead plus quercetin groups and quercetin groups. Rats were exposed to lead acetate in the drinking water (500mgPb/L) with or without quercetin co-administration (25 and 50mgQU/kg intragastrically once daily). After 75days, serum uric acid, urea, creatinine, renal reactive oxygen species (ROS) production, thiobarbituric acid reactive substances (TBARS) and histopathological analysis were performed. Pb content in kidney was also assayed. The levels of tumor necrosis factor-alpha (TNF-α), interleukin-1beta (IL-1β), interleukin-6 (IL-6), cyclooxygenase-2 (COX-2), the extracellular-receptor kinases (ERK1/2), the c-Jun N-terminal kinases (JNK1/2), p38 MAPK and nuclear factor-κB (NF-κB) were measured. Quercetin significantly prevented Pb-induced nephrotoxicity in a dose-dependent manner, indicated by both diagnostic indicators and histopathological analysis. Quercetin significantly decreased Pb content in kidney. Pb-induced profound elevations of oxidative stress in kidney were suppressed by quercetin. Furthermore, quercetin significantly inhibited Pb-induced inflammation in rat kidney. These results suggest that quercetin has the nephroprotective actions. The inhibition of Pb-induced kidney inflammation by quercetin is due at least in part to its anti-oxidant activity and its ability to modulate the MAPK and NF-κB signaling pathway. Quercetin might be a potent nephroprotective drug to protect Pb-induced kidney injury. [Display omitted] ► Quercetin prevented Pb-induced nephrotoxicity. ► Quercetin reduced Pb-induced increase in ROS and TBARS production in kidney of rats. ► Quercetin inhibited the inflammatory cytokine expression in kidney of Pb treated rats. ► Quercetin suppressed the MAPKs and NF-κB activation in rat kidney. ► Quercetin inhibited the Pb-induced oxidative stress and inflammation.